Social Media Use Among Library and Information Science Students: A Case Study - Mathias Gabriel Kasa; Jamilu Muhammad Isah; Mohammed Shehu; Shehu Allahde; Sunday Ladipo (MO.RI Publishing, 2021)
The purpose of this study is to identify the prevailing conditions of social media use among undergraduate students of Library and Information Science in a Nigerian University. Simple random sampling technique was used to select a sample of 180 full-time undergraduate students purposely. Descriptive statistics was used to analyze data collected through the administration of questionnaire. Research findings showed that a great number of students of Library and Information Science are addicted to social media for wrong academic purposes. The levels of addiction varied according to four Likert scale type. The highly addiction was among student using WhatApp (40.82%) and not addicted among students using BB chat (13.12%). The demographic indicators provided the obvious results of singles (77.78%) possessing prevalence tendency of addiction, and surprisingly those between the ages of 27-30 (40%) were most addicted. The paper recommends awareness programmes that are tailored to reveal the ills of social media addiction and pave ways to balance use of social media platforms that benefit academic activities among students.